2020
DOI: 10.1111/1751-2980.12854
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the diagnosis and treatment of hepatic fibrosis (2019)

Abstract: Hepatic fibrosis is a reparative response of diffuse over‐deposition and abnormal distribution of extracellular matrix (collagen, glycoprotein and proteoglycans) after exposure to various kinds of liver injuries, and is a key step in the developmental process of various chronic liver diseases leading to cirrhosis. Recently, many advances in our understanding of hepatic fibrosis have been obtained through basic and clinical research. Therefore, this consensus summarizes and offers 15 evidence‐based recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Therefore, FibroScan was used to track the improvement in liver stiffness brought on by TCM, and the results showed that the rate of improvement after treatment was 40.63%, which was much better than the 28.79% of the TCM nonusers. APRI and FIB-4 are relatively mature serum noninvasive detection models, in which the sensitivity and specificity of APRI in evaluating liver fibrosis after hepatitis B are 0.87 and 0.66 [ 18 ] and of FIB-4 are 0.78 and 0.65 [ 19 ], respectively. According to results of our research, both of them effectively predicted the improvement of TCM on liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FibroScan was used to track the improvement in liver stiffness brought on by TCM, and the results showed that the rate of improvement after treatment was 40.63%, which was much better than the 28.79% of the TCM nonusers. APRI and FIB-4 are relatively mature serum noninvasive detection models, in which the sensitivity and specificity of APRI in evaluating liver fibrosis after hepatitis B are 0.87 and 0.66 [ 18 ] and of FIB-4 are 0.78 and 0.65 [ 19 ], respectively. According to results of our research, both of them effectively predicted the improvement of TCM on liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of 1.5 cm of liver tissue with at least 6 portal tracts was required for diagnosis. According to Scheuer's classification, the degree of inflammatory activity and fibrosis were divided into 0–4 grades (G) and 0–4 stages (S) ( 19 ) by two pathologists blinded to the clinical data. G1-2, S0-2 were defined as mild-moderate CHB; G3, S1-3 were defined as severe CHB, G4, S2-4 were defined as cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
“…G1-2, S0-2 were defined as mild-moderate CHB; G3, S1-3 were defined as severe CHB, G4, S2-4 were defined as cirrhosis. When the opinions of the two experts were inconsistent, the higher G score was used ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…As per Scheuer’s classification ( 15 ), two pathologists who were blinded to the clinical data performed the histological grading of necro-inflammation (G0–G4) and the staging of liver fibrosis (S0–S4). SHCHI were established as grade ≥ G2 inflammation and/or stage ≥ S2 fibrosis ( 16 ). According to the definition of SHCHI in literature 16, the five levels of inflammation and fibrosis were classified into two categories, but the five levels were not compared separately ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%